The effect of different seed dormancy breaking treatments on optimizing seed germination of Echinophora platyloba - Behrooz Salehi-Eskandari; Farzaneh Aslani (علوم و فناوری بذر ایران)
Echinophora platyloba is an aromatic perennial plant belonging to the family Apiaceae which is used as food seasoning and persevering in Iran and the shoots have medicinal properties. This study aimed to investigate treatments of moist chilling (0,30, 45, 70 and 90 days), gibberellic acid (GA3; 0, 500, 1000 and 2000 mg/L) and scarification alone or a combination of these treatments for breaking seed dormancy of E. platyloba. The dormancy of the seeds was broken only after 90 days of moist chilling. Pretreatment GA only at the highest level (2000 mg/L) could induce seed germination (GP; 33%), the highest GP (50%) and germination index (GR; 3 seeds per day) was recorded in moist chilling treatment 45 days with GA3 treatment of 1000 mg/L. The lowest of GR was related to moist chilling treatment for 90 days and moist chilling treatment for 30 and 70 days with GA3 treatments of 500 and 2000 mg/L. The scarification treatment alone or combined with other treatments does not affect germination parameters.